2018
DOI: 10.1074/jbc.ra117.000633
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of cross-talk between the cell-surface proteins CD36 and CD47–TSP-1 in osteoclast formation and function

Abstract: Antibody-mediated blockade of cluster of differentiation 47 (CD47)-thrombospondin-1 (TSP-1) interactions blocks osteoclast formation and attenuates parathyroid hormone (PTH)-induced hypercalcemia in mice. Hypercalcemia in this model reflects increased bone resorption. TSP-1 has two cell-associated binding partners, CD47 and CD36. The roles of these two molecules in mediating the effects of TSP1 in osteoclasts are unclear. Osteoclast formation was attenuated but not absent when preosteoclasts isolated from CD47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…CD47 was found to be involved primarily in the cell fusion of small osteoclasts in the early stages of osteoclastogenesis and mononucleated pre-osteoclasts [ 100 , 101 ], but it seems not to be the only ligand for MFR. A recent study has revealed that blocking MFR with a neutralizing antibody completely inhibits osteoclastogenesis of bone marrow cells even under RANKL and M-CSF stimulation [ 102 ], which did not occur when CD47-MFR signaling was blocked. Another ligand, CD36, also expresses on the surfaces of preosteoclasts and participates in MFR-mediated osteoclastogenesis.…”
Section: Cd47-mfrmentioning
confidence: 99%
See 1 more Smart Citation
“…CD47 was found to be involved primarily in the cell fusion of small osteoclasts in the early stages of osteoclastogenesis and mononucleated pre-osteoclasts [ 100 , 101 ], but it seems not to be the only ligand for MFR. A recent study has revealed that blocking MFR with a neutralizing antibody completely inhibits osteoclastogenesis of bone marrow cells even under RANKL and M-CSF stimulation [ 102 ], which did not occur when CD47-MFR signaling was blocked. Another ligand, CD36, also expresses on the surfaces of preosteoclasts and participates in MFR-mediated osteoclastogenesis.…”
Section: Cd47-mfrmentioning
confidence: 99%
“…CD36 and CD47 double-knockout osteoclasts showed impaired resorptive activity in vitro. Surprisingly, however, double-knockout mice did not have a significantly abnormal bone phenotype [ 102 ], whereas CD36-deficient mice and MFR-deficient mice both showed an osteopetrotic phenotype [ 102 , 103 ]. Therefore, other unknown factors seem to be involved in MFR-mediated osteoclast multinucleation.…”
Section: Cd47-mfrmentioning
confidence: 99%
“…(1) Anti-inflammatory and antiangiogenesis by binding to TSP-1 (2) Proinflammatory (3) Profibrogenic Wu et al [35] Rustenhoven et al [68] Koduru et al [67] BioMed Research International ligand 1 (PD-L1), which can lead to the immune escape of cancer cells and promote the development of inflammation. In addition, MIF/CD74 can also regulate the expression of inflammatory factors, such as IL-6 and IL-8.…”
Section: Cd47mentioning
confidence: 99%
“…During osteoclast formation, TSP-1 promotes osteoclast formation, angiogenesis, inflammatory response, apoptosis, and fibrosis by binding CD47 and CD36 receptors to inhibit the production and signaling transduction of NO and cGMP signals. CD36, another important regulator of inflammation, has many ligands similar to CD47 [ 67 ]. In addition to CD47, CD36 is an important receptor for TSP-1.…”
Section: Interaction Between Cd47 and Other Factorsmentioning
confidence: 99%
“…As pre-osteoclasts migrate and extend membrane protrusions, they eventually find fusion partners and form large multinucleated cells. Osteoclast fusion is mediated by numerous proteins, including DC-STAMP and the interaction of CD47 and thrombospondin-1 (THBS1) [44]. In human PBMCs, the contribution of THBS1 in fusion is fine-tuned by hsalet-7e, which is upregulated with differentiation and targets Thbs1 transcripts [16].…”
Section: Mirnas Regulating Pre-osteoclast Maturationmentioning
confidence: 99%